Application of Legal Provisions and Liability for Maritime Autonomous Surface Ships (MASS) in International Law - Rantung, Esterlita Nova Yaser; Kosho, Philippa Philomena (Balobe Law Journal, 2025)
Introduction: Technological developments in the maritime sector have led to innovations such as unmanned surface vessels (Maritime Autonomous Surface Ships/MASS). The emergence of MASS brings efficiency, safety, and new innovations to the world of shipping, but it also poses legal challenges, particularly regarding the application of international regulations that have traditionally governed manned vessels.Purposes of the Research: This study aims to analyze the application of legal provisions and identify liability mechanisms for MASS under international law, as well as compare practices across several countries.Methods of the Research: The methodology employed is normative legal research using a legislative, comparative legal, and conceptual approach, utilizing primary legal sources such as international conventions (UNCLOS, SOLAS, and IMO regulations) and relevant literature.Results of the Research: The results of the study indicate that most international legal instruments have not yet fully accommodated the characteristics and regulatory needs of autonomous ships, particularly in terms of the definition of legal subjects, the role of the captain, and accountability mechanisms in the event of an incident. This is because most of these international legal provisions are still based on the assumption that ships are controlled by humans. Some countries, such as the United Kingdom, Norway, and the United States, have begun to formulate specific regulations to govern MASS that can fill this gap. Therefore, accountability is needed, which indicates the need for updating and harmonizing international rules to address the challenges arising from technological developments in the maritime sector. Additionally, it is important to develop national implementation guidelines aligned with the principles of international maritime law to ensure maritime safety, marine environmental protection, and legal certainty.